Remapping Internal Migration: How Complex Are Indonesian Migration Trajectories? - Widaryoko, Nanang; Sukamdi,; Pitoyo, Agus Joko (Journal of Population and Social Studies [JPSS], 2023)
Most conventional perspectives depict internal migration as a simple one-step process. Indeed, it simplifies complex migration patterns while concealing the diversity of migration dynamics throughout the life course. This study looks into the possibility of other types of migration in Indonesia besides one-way movement. Using sequence analysis on longitudinal data, we identify complex migration trajectories among Indonesians aged 12 to 50. Multinomial regression analysis confirmed that specific migration trajectories are associated with specific sociodemographic characteristics. This finding implies that migration takes a variety of paths and constantly evolves.